Dissecting aneurysm of the proper hepatic artery after laparoscopic hepatectomy possibly related to the Pringle maneuver: A case report. Issue 3 (24th January 2022) - Kurimoto, Makoto; Seo, Satoru; Yoh, Tomoaki; Shimizu, Hironori; Masano, Yuki; Ogiso, Satoshi; Anazawa, Takayuki; Ishii, Takamichi; Hata, Koichiro; Masui, Toshihiko; Taura, Kojiro; Hatano, Etsuro
Abstract: In hepatectomy, the Pringle maneuver is commonly used, but its association with iatrogenic injury is not yet well understood. This report presents a case of dissecting aneurysm of the proper hepatic artery (PHA) possibly associated with the Pringle maneuver during laparoscopic hepatectomy, that was successfully treated by transcatheter arterial embolization (TAE). The patient was a woman in her 70s, and repeat hepatectomy for liver metastasis of rectal neuroendocrine neoplasm was planned. She underwent hand‐assisted laparoscopic hepatectomy with the Pringle maneuver. On postoperative day (POD) 7, enhanced computed tomography showed a dissecting aneurysm of the PHA. TAE of the PHA to prevent hemorrhage was performed on POD 9 with no complications. Even after TAE, intrahepatic arterial flow was provided by the peribiliary arteries. This case suggests the possibility that the Pringle maneuver can cause a dissecting aneurysm of the hepatic artery.